Barney Glaser: Remembering a Genius - Odis E. Simmons (Grounded Theory Review: An International Journal, 2022)
I was introduced to the ideas of Barney Glaser in 1967 when I was an undergraduate student at Sonoma State College (now University). I was pondering what field to declare as my major subject. I was interested in sociology, but after reading several randomly selected works of classic and contemporary sociology theorists, I had doubts. These works were written for an academic audience and at that time I didn’t envision myself as an academic. Also, I couldn’t imagine myself being able to write anything like what I was reading. While browsing through the sociology section in the campus bookstore, I came across Glaser & Strauss’ The Discover of Grounded Theory. After skimming through it, I decided to buy it, take it home, and read it. It really grabbed me. This book sealed my interest in sociology and prompted me to declare it as my major.